The Influence of Perceived Ease of Use, Usefulness, and Trust on Consumer Purchase Interest in the TikTok Shop Yellow Cart Feature - Muhammad Luthfi; Mochamad Freski Dino Fava; Ramadhan Abiyasa Harianto Harianto; Muhammad Farhan Al Ghifari (Universitas Negeri Surabaya, 2026)
The social commerce phenomenon has transformed consumer shopping behavior by integrating entertainment and online transactions. TikTok Shop, through its